Understanding human capital development through soft skills requirements in Islamic perspective / Noor Malinjasari Ali, Rahayu Izwani Borhanuddin and Raslina Mohamed Nor - Ali, Noor Malinjasari; Borhanuddin, Rahayu Izwani; Mohamed Nor, Raslina (2012)
The growing interest on the quality of graduates produced by local higher education centers has led many inquiries into the need for human capital management in universities. Since higher education centers are going through a process of transformation, the aim of producing high quality graduates becomes greater. Intangible assets are seen as the soft skills necessary for the human capital development of university graduates namely generic abilities, innovation strategy and positive attitude, that are expected by industry players. University has the reponsibilities of bringing out the best values in their students through formal and informal learning. The development of human capitals with right principles will give identity to society and country. Graduates are given credit to define future generation. Thus, despite their excellence in academic achievement, having the necessary soft skills in life will improve the quality and qualification of an individual. With this quality, it is not impossible for Malaysia to become a developed nation by 2020 through the development of soft skills that reflects the education system in the country and in a way that is parallel with Islamic laws and regulations.